2020
DOI: 10.3390/ijerph17249520
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Policy Differences across US States: Shutdowns, Reopening, and Mask Mandates

Abstract: This work used event study to examine the impact of three policies (shutdowns, reopening, and mask mandates) on changes in the daily COVID-19 infection growth rate at the state level in the US (February through August 2020). The results show the importance of early intervention: shutdowns and mask mandates reduced the COVID-19 infection growth rate immediately after being imposed statewide. Over the longer term, mask mandates had a larger effect on flattening the curve than shutdowns. The increase in the daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 39 publications
1
69
1
Order By: Relevance
“…Only Wibbens et al 18 assessed the impact of NPIs until November 2020 and Pozo-Martin et al 19 performed a first analysis of the initial phase of the pandemic and a second from October until December 2020. Zhang et al 20 analysed another relatively long study period until August, and several authors performed an analysis until July 2020 21 , 22 , 23 . Some authors standardised the start and/or end of the study period in order to be able to compare the effectiveness of NPIs across units of analysis at similar stages of the epidemic 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only Wibbens et al 18 assessed the impact of NPIs until November 2020 and Pozo-Martin et al 19 performed a first analysis of the initial phase of the pandemic and a second from October until December 2020. Zhang et al 20 analysed another relatively long study period until August, and several authors performed an analysis until July 2020 21 , 22 , 23 . Some authors standardised the start and/or end of the study period in order to be able to compare the effectiveness of NPIs across units of analysis at similar stages of the epidemic 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the geographical scope, eleven studies analysed more than 65% of the world's territories 16 , 17 , 21 , 23 , 32 , 33 , 34 , 35 , 36 , 37 , 38 . Some focused on specific areas, with nine studies analysing data from the United States, performing mostly state-level 20 , 26 , 31 , 39 , 40 , 41 , but also county-level 22 , 42 , 43 analyses, three studies estimating the effects of NPIs in Europe 28 , 29 , 44 and two studies in all OECD countries 19 , 45 . Five studies selected specific countries that belong to different world regions 15 , 24 , 25 , 30 , 46 and three included both countries and US states 18 , 27 , 47 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…History tells us that adopting and adhering to public health measures - Comparative Policy Analysis of COVID-19 135 some as simple as mask wearing, social distancing, limiting indoor gatherings -were crucial for slowing down the 1918 flu pandemic (Markel et al 2007). Early observations have indicated that rapid and coherent policy responses (interventions) have determined the trajectory of the COVID-19 crisis in any given country (Capano 2020;Mei 2020;Migone 2020;Rocco et al 2020;Zhang and Warner 2020). Sadly, these measures have become politicized in many countries.…”
Section: Politics Of Crisis Policy Responses: Partisanship Intergovernmental Relationship and State-society Tensionmentioning
confidence: 99%
“…Policy scholars have long sought to understand why governments respond similarly or differently to the same problem and how policies work in different contexts (Baekkeskov 2016;Capano and Lippi 2016;Geva-May et al 2018), but rarely does the same policy challenge occur at the same time and with the same intensity in different international locations. Facing the same, unknown coronavirus, national and subnational units have responded with degrees of similar or different sets of interventions and measures, adopted at similar or different points in time, enforced with similar or different degrees of intensity, met with similar or different levels of compliance, and sustained over similar or different time spans during 2020-2021 (Capano et al 2020;Downey and Myers 2020;Hale et al 2020;IMF 2020;Mei 2020;OECD 2020;Yan et al 2020;Zhang and Warner 2020). Under these extraordinary circumstances, the comparative lens can lend a better understanding of the commonalities and dissimilarities of policy responses that countries have adopted in crisis situations, and the conditions of their adoption and effectiveness, thereby identifying the lessons that can be drawn and extrapolated across contexts.…”
Section: Introductionmentioning
confidence: 99%